Controllable fabrication of TiO2 anatase/rutile phase junctions by a designer solvent for promoted photocatalytic performance. Issue 79 (3rd September 2020) - Wang, Qian; Fang, Xinxin; Hao, Pin; Ren, Huaiyan; Zhao, Yingqiang; Huang, Fang; Xie, Junfeng; Cui, Guanwei; Tang, Bo
Abstract : Highly active coin tree-like TiO2 anatase–rutile phase junctions were constructed by tailored DESs and the two-phase ratios can be easily tuned. Abstract : Herein, novel coin tree-like TiO2 moieties with lots of anatase–rutile phase junctions were constructed by a general, simple, and environmentally friendly strategy. The anatase/rutile ratios can be easily tuned by changing the ratios of the two H-bond donors. Owing to this featured shape, the TiO2 sample displays robust photocatalytic activity and better stability.